2018
DOI: 10.1016/j.ijscr.2018.07.047
|View full text |Cite
|
Sign up to set email alerts
|

A long-term survivor of undifferentiated carcinoma of the liver successfully treated with surgical treatments: A case report and literature review

Abstract: HighlightsUndifferentiated carcinoma of the liver is extremely rare disease.We experienced a long-term survivor of undifferentiated carcinoma of the liver successfully treated with radical hepatectomy.The tumor showed a huge hypovascular cystic mass with ring enhancement and partial solid component.It might grow quickly and show necrosis at the center of the tumor, making it difficult to distinguish from liver abscess.This disease has markedly different clinical and biological features from common primary mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Masatsugu et al. described radical surgery without any chemotherapy for an undifferentiated liver tumor that achieved good results ( 31 ). According to Hood et al., a woman with recurrent OCGT of the liver was treated with 5-fluorouracil and adriamycin, external beam radiation, and radioimmune therapy (IgG, labeled with I-131) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Masatsugu et al. described radical surgery without any chemotherapy for an undifferentiated liver tumor that achieved good results ( 31 ). According to Hood et al., a woman with recurrent OCGT of the liver was treated with 5-fluorouracil and adriamycin, external beam radiation, and radioimmune therapy (IgG, labeled with I-131) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…While undifferentiated carcinoma of the liver lacks a definitive treatment protocol [1][2][3], nivolumab, an immuno-checkpoint inhibitor, has shown promise for those cases classified under the 'poor prognosis group' of cancers of unknown primary [10]. These elusive cancers are bifurcated clinically and pathologically into two main categories.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated carcinoma of the liver is a rare malignant neoplasm [ 1 , 2 ]. The clinicopathological features and progression of this carcinoma are not well-documented, and no definitive therapeutic approach exists for inoperable instances [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the relative rarity of UCDS and the lack of clinical trials, therapeutic guidelines or recommendations are not available (31). Literature reports have suggested a variety of regional and systemic treatment strategies; however, complete response and long-time survival were achieved in only a few cases (32,33). Reis Neto et al studied 287 patients with rectal adenocarcinoma treated with radiotherapy followed by surgery and reported that preoperative radiotherapy decreased the proportion of undifferentiated cells, indicating that undifferentiated rectal cancer cells were more sensitive to the radiation than differentiated cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%